2018
DOI: 10.1111/psyp.13084
|View full text |Cite
|
Sign up to set email alerts
|

Heartbeat counting is unrelated to heartbeat detection: A comparison of methods to quantify interoception

Abstract: Recent research has identified individual differences in interoceptive sensitivity as a key source of variation in action, cognition, and emotion. This research has relied heavily on a single method for assessing interoceptive sensitivity: the accuracy of counting heartbeats while at rest. The validity of this method was assessed here by comparing the heartbeat counting (HBC) performance of 48 individuals with their heartbeat detection (HBD) performance. The HBC task required participants to report the numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(155 citation statements)
references
References 66 publications
4
142
1
Order By: Relevance
“…Interoceptive accuracy is distinct from subjective conceptualization of one’s own interoceptive sensitivity (interoceptive sensibility assessed via self‐rated questionnaires) and metacognitive interoceptive awareness (insight; i.e., alignment of objective accuracy with subjective sensibility), which more precisely indexes conscious awareness of bodily signals (Garfinkel et al, ; Khalsa et al, ). Moreover, HB discrimination depends won perceptual discrimination between internal bodily cues and external stimuli, a process that is more cognitively demanding than heartbeat counting/tracking yet without the same confounding issues of time estimation, knowledge of one’s heart rate, and systematic underreporting of heartbeats (Ring & Brener, ; Zamariola et al, ; cf. Ainley, Brass, & Tsakiris, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interoceptive accuracy is distinct from subjective conceptualization of one’s own interoceptive sensitivity (interoceptive sensibility assessed via self‐rated questionnaires) and metacognitive interoceptive awareness (insight; i.e., alignment of objective accuracy with subjective sensibility), which more precisely indexes conscious awareness of bodily signals (Garfinkel et al, ; Khalsa et al, ). Moreover, HB discrimination depends won perceptual discrimination between internal bodily cues and external stimuli, a process that is more cognitively demanding than heartbeat counting/tracking yet without the same confounding issues of time estimation, knowledge of one’s heart rate, and systematic underreporting of heartbeats (Ring & Brener, ; Zamariola et al, ; cf. Ainley, Brass, & Tsakiris, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the heartbeat tracking task (Schandry, ), participants focus on and count their heartbeats over different time periods, and their reported number of felt heartbeats is compared to the actual number recorded. While this appears to be an easy way to implement direct measure of interoceptive experience, for which graded correlations across populations can usefully track affective variables (Dunn et al, ), tracking performance is influenced by factors including practice, ability to judge time, and knowledge of one’s heart rate (Ring & Brener, ; Zamariola, Maurage, Luminet, & Corneille, ). An alternative task, heartbeat discrimination (Whitehead, Drescher, Heiman, & Blackwell, ), requires participants to judge whether external stimuli (e.g., auditory tone) occur synchronously with one’s heartbeat.…”
Section: Introductionmentioning
confidence: 99%
“…143 Individuals with anorexia nervosa display reductions in functional connectivity in the thalamo−insula subnetwork, thought to reflect changes in the propagation of sensations that convey homeostatic imbalances. 30 Bulimia nervosa is associated with increased gray matter volumes within the ventral AI, 29 and binge ED is associated with increased insula activity when viewing food images after an overnight fast. 25 Interestingly, altered interoception is not only found in patients who are currently suffering from an ED.…”
Section: Eating Disordersmentioning
confidence: 99%
“…Indeed, Ainsley et al (2016) have previously characterised these individual differences in interoceptive ability as individual differences in relative precision of prediction errors. However, caution should be taken when interpreting differences across interoceptive ability groups, as multiple heartbeat detection paradigms exist, which assess distinct processes and may not measure interoceptive ability validly (Brener & Ring, 2016;Corneille et al, 2020;Ring & Brener, 2018). In addition, Garfinkel et al (2015) suggested three distinct and dissociable dimensions of interoceptive ability: interoceptive sensibility, accuracy, and awareness, with each dimension potentially influencing predictive mechanisms differently.…”
mentioning
confidence: 99%